2019
DOI: 10.1186/s13018-019-1188-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of both endplate nutritional pathways results in intervertebral disc degeneration in a goat model

Abstract: Background The vertebral endplate route was demonstrated to be the main pathway for nutrition to the intervertebral disc. However, it is still a controversial issue on whether the blocking of the endplate nutritional pathway could result in intervertebral disc degeneration (IDD) in animal models. The aim was therefore to investigate the effect of the inhibition of both endplate nutritional pathways by bone cement injection on the IDD in a goat model. Methods Two lumbar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…This phenomenon is not observed in the non‐chondrodystrophic dog breeds but is also seen in ovine models, making the sheep model a candidate for further characterization 33 . Additionally, the goat has been used as an effective translational model to evaluate the impact of disc nutrition and CEP permeability on the etiology of IVD degeneration 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is not observed in the non‐chondrodystrophic dog breeds but is also seen in ovine models, making the sheep model a candidate for further characterization 33 . Additionally, the goat has been used as an effective translational model to evaluate the impact of disc nutrition and CEP permeability on the etiology of IVD degeneration 34 …”
Section: Discussionmentioning
confidence: 99%
“…33 Additionally, the goat has been used as an effective translational model to evaluate the impact of disc nutrition and CEP permeability on the etiology of IVD degeneration. 34 This study provides valuable insight into species specific differences between the human, bovine and canine CEP on the structural, however, for the current study we focused on bovine because of its similarities to the structure and cell composition of the healthy human IVD 35 and the chondrodystrophic dog given its utility as a model for IVD degeneration and back pain. 16…”
Section: Cell Morphology and Gene Expressionmentioning
confidence: 99%
“…It is well known that, the nutritional pathways that into the nucleus pulposus of human intervertebral discs are mainly by diffusion through the central portion of the end-plate from these marrow space cartilage contacts [11]. Thus, a functional intact endplate is crucial to transport nutrients and waste products by diffusion [31,32].Dudli et al [8] characterized the process of disc degeneration using an in vitro full-organ model, and elucidated that burst endplates, but not equienergetic loading promoted disc degeneration. However, Chan et al [33] reported that, impact load which was generally sub-traumatic, could also cause cumulative damage and injury to the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that, the nutritional pathways that into the nucleus pulposus of human intervertebral discs are mainly by diffusion through the central portion of the end-plate from these marrow space cartilage contacts [11]. Thus, a functional intact endplate is crucial to transport nutrients and waste products by diffusion [31,32].Dudli et al [8] characterized the process of disc degeneration using an in vitro full-organ model, and elucidated that burst endplates, but not equienergetic loading promoted disc degeneration. However, Chan et al [33] reported that, impact load which was generally subtraumatic, could also cause cumulative damage and injury to the lumbar spine.…”
Section: Discussionmentioning
confidence: 99%